IMPLEMENTASI PEMBELAJARAN E-LEARNING MATEMATIKA SISWA KELAS IV MI AL-AZHAR MENGANTI GRESIK - Ivo Yuliana; Nur Jannah Wanda Hamidah; Ria Resti Fauziah (Pedir Research Institut, 2021)
COVID-19 pandemic, students are asked to study at home using e-learning that utilizes social media. The problems to be answered in this study are as follows: 1. How is the implementation of e-learning mathematics for class IV students at MI Al-Azhar Menganti Gresik?, 2. What are the supporting factors in implementing e-learning mathematics for class IV students at MI Al- Azhar Menganti Gresik?, 3. What are the inhibiting factors and solutions in the implementation of e-learning mathematics for fourth grade students of MI Al-Azhar Menganti Gresik?. This study uses a descriptive qualitative approach with the research subject of the principal, the head of the curriculum, class teachers and fourth grade students. Data collection methods used are observation, interviews and documentation. The data analysis used is the Miles and Huberman model with data reduction techniques, data presentation and conclusion drawing. The results of the research regarding the implementation of e-learning mathematics for fourth grade students of MI-Azhar is the implementation of learning that is carried out without direct face-to-face between teachers and students as well as accessing the internet network and using social media to exchange information and interactions Among them is by using the whatsapp application, google meet and youtube. Then the supporting factors for e-learning learning are the very rapid development of IT, a good and stable signal network. While the inhibiting factors for e-learning learning are the internet network which is less stable, the unavailability of internet package quotas.